REPRESENTASI NILAI KELUARGA PADA FILM PENDEK “KEMBALI PULANG” (ANALISIS ROLAND BARTHES) - Maskana; Silvina Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
The short film ‘Kembali Pulang’ tells the story of a girl’s life journey who only lives with her mother after her father leaves. Their relationship experiences various dynamics after the child decides to go abroad to pursue her dreams. The purpose of this study is to determine the representation of family values ​​in the short film “Kembali Pulang” through Roland Barthes’ Semiotic Analysis. This study is a descriptive qualitative study with Roland Barthes’ semiotic analysis method which includes three elements, namely denotation, connotation, and myth. Through a reflective approach, this film reflects common family values ​​in Indonesian culture, such as affection, care, togetherness, attention, warmth that is woven within the family, and forgiving each other for misunderstandings that occur. This film is a reflection media that reminds us of the importance of maintaining relationships with family, especially with both parents, and more appreciating togetherness, presence and affection of family in everyday life.